2006
DOI: 10.1021/ol0530272
|View full text |Cite
|
Sign up to set email alerts
|

Oxone as an Inexpensive, Safe, and Environmentally Benign Oxidant for C−H Bond Oxygenation

Abstract: [reaction: see text] This paper describes the application of peroxide-based oxidants in the Pd(OAc)(2)-catalyzed acetoxylation and etherification of arene and alkane C-H bonds. Oxone in acetic acid and/or methanol proved particularly effective, and these transformations were applied to a wide variety of substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
148
1
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(157 citation statements)
references
References 17 publications
4
148
1
4
Order By: Relevance
“…[1,[4][5][6][7][8] With respect to Pd catalysis, Yu and co-workers have pioneered the use of carboxylate groups as effective promoters of Pd-catalyzed selective CÀH functionalization, [5] which has led to seminal developments in cross-coupling with arylorganometallic reagents; [5a,b, 6] further developments have led to carbonylation, [5c] alkylation, [5d] olefination, [5e,f] oxygenation, [5g] and iodination [5h,i] reactions. Related to this, other carbonyl-based directing groups such as amide derivatives, [7] ketones, [8] and oximes [9] have also resulted in developments in catalytic CÀH bond functionalization. However, many of these groups impart a strong electron withdrawing effect on the parent aromatic nucleus, and hence the C À H bond palladation event often requires forcing reaction conditions that may not always be compatible with more delicate molecular architecture.…”
mentioning
confidence: 99%
“…[1,[4][5][6][7][8] With respect to Pd catalysis, Yu and co-workers have pioneered the use of carboxylate groups as effective promoters of Pd-catalyzed selective CÀH functionalization, [5] which has led to seminal developments in cross-coupling with arylorganometallic reagents; [5a,b, 6] further developments have led to carbonylation, [5c] alkylation, [5d] olefination, [5e,f] oxygenation, [5g] and iodination [5h,i] reactions. Related to this, other carbonyl-based directing groups such as amide derivatives, [7] ketones, [8] and oximes [9] have also resulted in developments in catalytic CÀH bond functionalization. However, many of these groups impart a strong electron withdrawing effect on the parent aromatic nucleus, and hence the C À H bond palladation event often requires forcing reaction conditions that may not always be compatible with more delicate molecular architecture.…”
mentioning
confidence: 99%
“…(Scheme 5) Palladium catalyzed coupling of 2-bromopyridine with boronic acid 33 in the presence of sodium carbonate in a mixture of water/ethanol and DME at 75 C within 16 h [54] afforded biaryl bromide 34 which was treated with sodium azide and copper(I) iodide according to the procedure of Liang and co-workers to deliver azide 15 [55]. Subsequently a palladium-catalyzed acetoxylation of arene CeH bond at ortho position to the pyridine-2-yl substituent has been performed by phenyliodine diacetate (PhI(OAc) 2 ) in acetic anhydride [56]. These conditions led regioselectively to azide 16 in 57% yield.…”
Section: Preparation Of Azides 15e21mentioning
confidence: 99%
“…In recent studies of oxidation of some model hydrocarbyl platinum(II) complexes Sanford et al showed that cyclometalated 8-methylquinoline platinum(II) acetylacetonate could be oxidized in alcoholic solutions by PhI(OAc) 2 to form a mixture of dialkoxy and acetoxy alkoxy platinum(IV) complexes (Scheme 12) [33]. The acetylacetonate was chosen as a model of organopalladium(II) intermediates involved in catalytic CH bond functionalization of N-donor heterocycles and some hydrocarbon derivatives [34][35][36][37][38][39][40]. When acetic acid was used as a solvent, a dinuclear acetato-bridged platinum(III) complex formed instead.…”
Section: Ii-c Pt II -C Bond Functionalization Relevant To Catalytic mentioning
confidence: 99%